Clinical management for epidermolysis bullosa dystrophica - Thais M. Oliveira; Vivien T. Sakai; Liliani A. Candido; Salete M. B. Silva; Maria Aparecida A. M. Machado (University of São Paulo, 2008)
Epidermolysis bullosa (EB) consists of a group of genetic hereditary disorders in which patients frequently present fragile skin and mucosa that form blisters following minor trauma. More than 20 subtypes of EB have been recognized in the literature. Specific genetic mutations are well characterized for most the different EB subtypes and variants. The most common oral manifestations of EB are painful blisters affecting all the oral surfaces. Dental treatment for patients with EB consists of palliative therapy for its oral manifestations along with typical restorative and periodontal procedures. The aim of this article is to describe two dental clinical treatments of recessive dystrophic EB cases and their specific clinical manifestations. The psychological intervention required during the dental treatment of these patients is also presented.